Applications de la methode de S.A. Tchapliguine a l’etude des mouvements avec circulation, dans le cas de l’obstacle circulaire: Applications of the S.A. Tchapliguine method to the study of movements with circulation, in the case of the circular obstacle - Bena, Dorin (Anal. Numér. Théor. Approx., 1982)
Not available.